Deep homology: a view from systematics. - Scotland, R (2010)
Over the past decade, it has been discovered that disparate aspects of morphology - often of distantly related groups of organisms - are regulated by the same genetic regulatory mechanisms. Those discoveries provide a new perspective on morphological evolutionary change. A conceptual framework for exploring these research findings is termed 'deep homology'. A comparative framework for morphological relations of homology is provided that distinguishes analogy, homoplasy, plesiomorphy and synapomorphy. Four examples - three from plants and one from animals - demonstrate that homologous developmental mechanisms can regulate a range of morphological relations including analogy, homoplasy and examples of uncertain homology. Deep homology is part of a much wider range of phenomena in which biological (genes, regulatory mechanisms, morphological traits) and phylogenetic levels of homology can both be disassociated. Therefore, to understand homology, precise, comparative, independent statements of both biological and phylogenetic levels of homology are necessary.